1990
DOI: 10.1128/jb.172.12.6637-6640.1990
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in Brucella spp. due to highly repeated DNA

Abstract: The species of Brucella are very closely related, but Brucella ovis does not express detectable amounts of a protein, designated BCSP31, that is common to the other species. We studied the lack of expression of BCSP31 by Southern analysis. DNAs from the B. ovis culture collection strains and field isolates were probed with a 1.3-kb HindIll fragment encoding BCSP31 of Brucella abortus. The probe hybridized to a 1.6-kb HindIII fragment of all B. ovis strains tested, showing that the gene is present in B. ovis bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 23 publications
0
43
0
2
Order By: Relevance
“…Identification by standard methods is difficult and timeconsuming and may be frustrated by the occurrence of intermediates. Very minor interstrain differences were seen by polyacrylamide gel electrophoresis of proteins (12) or in some analyses with restriction endonucleases (8,14,15 fingerprinting. Polymorphic markers are also called random amplified polymorphic DNA markers (7,19,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Identification by standard methods is difficult and timeconsuming and may be frustrated by the occurrence of intermediates. Very minor interstrain differences were seen by polyacrylamide gel electrophoresis of proteins (12) or in some analyses with restriction endonucleases (8,14,15 fingerprinting. Polymorphic markers are also called random amplified polymorphic DNA markers (7,19,20).…”
mentioning
confidence: 99%
“…Identification by standard methods is difficult and timeconsuming and may be frustrated by the occurrence of intermediates. Very minor interstrain differences were seen by polyacrylamide gel electrophoresis of proteins (12) or in some analyses with restriction endonucleases (8,14,15). Allardet-Servent et al (1) found DNA polymorphism in Brucella strains only by using low-cleavage-frequency restriction enzymes such as XbaI or NotI.…”
mentioning
confidence: 99%
“…A close relationship has been found between B. melitensis and B. abortus, while an extreme divergence of B. ovis and B. neotomae from the other species was observed. This divergence may be the result of a gene conversion for this locus in these two species [48]. In this study, we found that B. neotomae strains are only partially susceptible to Tb phage, producing a few isolated plaques at RTD.…”
Section: Discussionmentioning
confidence: 59%
“…Division of the genus into species and biovars is based solely upon a small number of metabolic traits, two lipopolysaccharide epitopes, and sensitivity to a set of phage that are host-range variants of the same ancestor [48]. Although phage susceptibility to different species is evident, it indicates the significance of phage typing as a tool for Brucella species differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Este elemento está presente em cinco ou mais cópias no genoma de Brucella spp., mostrando ser completamente estável em número e posição no cromossomo (Halling & Zehr 1990, Bricker & Halling 1994, Bricker & Halling 1995. Entretanto, diferenças no número de elementos foram relatadas, como o biovar 1 de Brucella abortus que possui sete cópias (Ouahrani et al 1993, Bricker & Halling 1995, Ocampo-Sosa & García-Lobo 2008.…”
Section: Introductionunclassified